Impact of Advertising and Marketing Mix on buy trends of customer towards Herbal Products in India: Examining the Influence of Advertising and Marketing Mix on Consumer Buying Patterns of Herbal Products (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In today's world, people are becoming more aware of the dangers posed by manufacturedgoods such as medicine, food, and other items that are made with human-made chemicals thatcontaminate the environment. This has resulted in increased awareness of the environment and people'sown well-being, resulting in shifts in buyer inclinations and purchases. Purchasers are now consideringthe item's impact on their health and well-being. Green marketing has risen as a result of this. Growinggreen advertising has aided in the expansion of the market for homegrown products as well as thenumber of consumers who buy them.There is currently a large display of herbal products made with herbs such as cucumber, tamarind, andAloe Vera. Their popularity is growing, which is causing the industry to increase. As a result, businessesare focusing their efforts on producing homegrown products such as organic cleanser and homegrownfacial care products, among other things. Regular and home grown things are more popular amongIndian customers. In India, the natural item sector is predicted to grow at a pace of 12.Herbalists have developed strategies to penetrate additional Indian marketplaces in this way. In anycase, there is still a lack of demand for homegrown products assembled in India. The goal of this studyis to measure the effects of marketing mix on consumer buying patterns. The study looked at the four'P's of marketing product, pricing, location, and promotion.A systematic questionnaire was used to conduct the survey. The study's sample size was determined tobe 384.After removing the faulty questionnaires, a total of 297 items were considered for the study. Thestudy's findings revealed that brand and advertisement have a substantial impact on consumer buytrends, however cost and location variables had no influence on the purchase patterns of consumerswho use herbal brands.